The hullaballoo over e-learning? Technology and pluralism in economics - Duncan Watson; Louise Parker (Cogent Economics & Finance, 2016)
E-learning vs. face-to-face delivery: this binary opposition has governed much of the existing pedagogical research concerning technological innovation, as educationists are pressured to prioritise efficiency and the cost-effectiveness of traditional teaching methods. This paper rejects such a false dichotomy, proffering the alternative that can be found in blended learning methods. It is through the meticulous splicing of e-learning and traditional lectures that the individual economics lecturer is freed to deliver a pluralist perspective. "Contest and controversy; orthodoxy and heterodoxy; critique and reject": technology provides the vehicle for economics education to break free of the constraints of monist teaching methods and ensures that economics students can fully engage in the discipline's vibrant debates.
Keywords: 330; e-learning; pluralism; technology; blended learning; economic tools for teaching